The Role of Multimodal Feedback (Audio and Video) from Educators in Enhancing Students' Essay Quality: A Qualitative Perspective - Fini Widya Fransiska1; Muhammad Rizky Al Fatih (Universitas Muhammadiyah Lampung, 2023)
This qualitative study explores the functions and mechanisms of multimodal feedback (audio and video) provided by instructors on the quality of Business English essays written by third-semester students, as well as the detailed revision strategies used by the students. Using a collective case study approach with 10 students and 2 instructors, data were gathered through triangulation methods, including document analysis (initial drafts and revisions), in-depth interviews, and observation of the revision process. The main findings reveal that multimodal feedback significantly reduces students' cognitive load when interpreting corrections, especially in improving macro-structure, cohesion, and coherence by offering contextual clarity (visualising errors) and pedagogical empathy (the instructor’s voice). This enhancement in cognitive understanding and social presence notably encourages transformational (deep-level) revisions, with over 60% of improvements focused on content and argument structure. The study recommends shifting from vague textual feedback to a multimodal digital approach to foster greater student accountability and ownership of their writing quality.